Питання визначення та використання логістичного потенціалу території - ZRYBNIEVA, IRYNA (Чернівецький національний університет, 2018)
In current conditions of the Ukrainian economy development, issues of determination and use of the territory logistical potential will provide opportunities for reducing the share of logistics costs in the structure of the cost of goods. The logistics potential is understood as the ability of a logistical regional system to ensure the timely movement of material resources through the use of storage, transport, personnel and climatic and geographic resources in the region and largely determines its competitiveness in the background of other regions, which can also be centers of transport and logistics activity.
ISSUES OF DETERMINATION AND USE OF THE TERRITORY LOGISTICAL POTENTIAL
Keywords: LOGISTICAL POTENTIAL; POTENTIAL; logistics activity; logistics; competitiveness